Analisis Motivasi Dan Pengetahuan Investasi Terhadap Minat Investasi Mahasiswa di Pasar Modal - Eny Suyanti; Nafik Umurul Hadi (FKIP Unswagati, 2019)
Students are the driving force of the financial industry in the capital market. Students are of special concern in the BEI capital market education program. IDX provides facilities by establishing investment galleries in several universities to support socialization and education programs. At present STKIP PGRI Tulungagung founded the Investment Gallery of the Indonesia Stock Exchange (GI BEI). Through the investment gallery, it is expected to be able to attract more new issuers and increase the number of investors in the capital market from among students and the campus environment. This study aims to analyze the effect of investment motivation on interest in investing in the capital market and the effect of investment knowledge on the interest in investing in the capital market in STKIP PGRI Tulungagung Economics Study Program students. This research uses Partial Least Square (PLS) Data Analysis Technique with three latent variables namely investment motivation, investment knowledge, and investment interest. The results of this study indicate that: (1) There is an influence of investment motivation on investment interest. This means that the higher the investment motivation, the more likely it is to increase investment interest with a path coefficient of 0.462 with a T statistics value of 5.170. The test results show that the path coefficient is positive with a value of T statistics> T table (1.64), (2) There is an effect of investment knowledge on investment interest with a path coefficient of 0.456 with a value of T statistics of 4.717. The test results show that the path coefficient is positive with the value T statistics> T table (1.64). The results of the analysis inform the variables that have the greatest path coefficient on investment interest are investment motivation with a path coefficient of 0.462, meaning that investment motivation is the variable that gives the most dominant influence.